Dampak Kebijakan terhadap Aktivitas Pedagang dan Juru Parkir: Studi Kasus Alih Fungsi Lahan Parkir Abu Bakar Ali Kota Yogyakarta - Samuel Aron Jedyjah Makmur; Muhammad Izzudin Aprilian; Fransisca Dea Yulianti; Henggaringtyas Trihandari Damayanti (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2026)
The purpose of this research is to determine the impact of the policy to convert the Abu Bakar Ali (ABA) parking area toward vendors and parking attendants. The data collection technique used was descriptive qualitative research, obtained from in-depth interviews with vendors and parking attendants and observations at the relocation site of the Malioboro Abu Bakar Ali 2 Parking Area. The Abu Bakar Ali parking lot conversion policy was an effort by the Yogyakarta City Government to improve the aesthetics of the Malioboro area and preserve cultural heritage. The findings reveal a significant gap between the environmental and cultural objectives of the policy and the socio-economic reality, with low tourist visitation to the new location resulting in a drastic decrease in income, leading to resentment among vendors and parking attendants. Therefore, the Yogyakarta City Government needs to review the implementation of this policy so that it does not lead to horizontal conflicts between the government and the vendors and parking attendants.